2015
DOI: 10.1016/j.neuroimage.2015.02.055
|View full text |Cite
|
Sign up to set email alerts
|

EEG imaging of toddlers during dyadic turn-taking: Mu-rhythm modulation while producing or observing social actions

Abstract: Contemporary active-EEG and EEG-imaging methods show particular promise for studying the development of action planning and social-action representation in infancy and early childhood. Action-related mu suppression was measured in eleven 3-year-old children and their mothers during a 'live,' largely unscripted social interaction. High-density EEG was recorded from children and synchronized with motion-captured records of children's and mothers' hand actions, and with video recordings. Independent Component Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 61 publications
(77 reference statements)
4
31
0
1
Order By: Relevance
“…This and other examples (Deák et al., ; Goldstein & Schwade, ; Jasso Triesch, Deak & Lewis, ; Yu & Smith, ) demonstrate the potential for microbehavioral and sequential analyses to answer questions about the development of complex social activity. Although changing patterns of brain activity during social interactions remains elusive (but see Liao, Acar, Makeig, & Deák, ), and higher order mental representations remain hypothetical, sensorimotor activity between partners is overtly measurable and rich. By focusing on changes in the microbehavioral dynamics of dyadic sensorimotor activity of infants and parents in natural settings over the 1st year, we can construct a new, more ecologically grounded account of the development of triadic attention and other social practices.…”
Section: Discussionmentioning
confidence: 99%
“…This and other examples (Deák et al., ; Goldstein & Schwade, ; Jasso Triesch, Deak & Lewis, ; Yu & Smith, ) demonstrate the potential for microbehavioral and sequential analyses to answer questions about the development of complex social activity. Although changing patterns of brain activity during social interactions remains elusive (but see Liao, Acar, Makeig, & Deák, ), and higher order mental representations remain hypothetical, sensorimotor activity between partners is overtly measurable and rich. By focusing on changes in the microbehavioral dynamics of dyadic sensorimotor activity of infants and parents in natural settings over the 1st year, we can construct a new, more ecologically grounded account of the development of triadic attention and other social practices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several EEG hyperscanning studies have attempted to identify such oscillations. One major finding is that alpha suppression is observed commonly in interaction tasks, such as a turn‐taking game [Liao et al, ], the Rock–Paper–Scissors game [Perry et al, ], joint attention [Lachat et al, ], vision‐based motor tasks [Naeem et al, ; Naeem et al, ], finger tapping [Konvalinka et al, ], and action observation [Ménoret et al, ]. Previous EEG hyperscanning studies have focused on natural interactions, such as playing a card game and a guitar together, visual interactions, imitating a hand movement, and joint attention.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this work, we designed a turn‐taking verbal interaction based on number counting without any visual input, and used simultaneous EEG and MEG measurements to find common oscillations on the part of all subjects and phase synchronization between two subjects. EEG alpha synchronization may yield significant oscillatory changes and phase synchronization in interaction tasks [Konvalinka et al, ; Lachat et al, ; Liao et al, ; Perry et al, ; Ménoret et al, ]. Further, MEG gamma band activity may play a critical role in social interaction [Pavlova et al, ], speech processing [Palva et al, ], and working memory [Jensen et al, ; Jokisch and Jensen, ].…”
Section: Introductionmentioning
confidence: 99%
“…Alpha or "mu rhythm" suppression has been well-documented in infants and young children in relation to both action production and action observation (Liao et al, 2015). For example, Marshall et al (2011) reported suppression effects in the 6-9 Hz range, broadly distributed over the scalp, when 14-month old infants were engaged in action observation in a social context.…”
Section: Discussionmentioning
confidence: 99%